Ambient versus household PM2.5 exposure and socioeconomic disparities in intracerebral hemorrhage burden: a 32-year global analysis (1990–2021) with projections to 2050 - Wu, Erman; Su, Riqing; Tang, Tong; Zhu, Guohua; Geng, Dangmurenjiafu (Frontiers in Public Health, 2025)
BackgroundWhile hypertension dominates intracerebral hemorrhage (ICH) risk globally, PM2.5 exacerbates health inequities through distinct ambient (APMP) and household (HAP) exposure pathways. Quantifying PM2.5-attributable burden across socioeconomic gradients remains critical for targeted intervention.MethodsUsing Global Burden of Disease (GBD) 2021 data, we analyzed age-standardized mortality (ASMR), disability-adjusted life years (DALYs), years lived with disability (YLDs), and years of life lost (YLLs) for PM2.5-attributable ICH. Joinpoint regression assessed trends (AAPC), while Bayesian Age-Period-Cohort modeling projected burdens to 2050. Pollution sources (APMP/HAP) were stratified by Socio-demographic Index (SDI).ResultsGlobally, PM2.5 caused 995,650 ICH - related deaths and 24,015,340 DALYs in 2021. From 1990 to 2021, the ASMR and disability rates for ICH due to PM2.5 exposure showed consistent declines globally (ASMR: −52.4%, DALYs: −53.1%, YLL: −53.4%, YLD: −40.7%), driven by HAP reductions. However, the absolute number of deaths and YLDs rose. The AAPC of the PM2.5 - related ICH burden also declined in the past 30 years. Nevertheless, projections indicate that by 2050, the PM2.5 - related ICH burden will increase. Low SDI regions exhibited 24.7 times higher ASMR than those in high SDI areas. Regionally, Asian regions (East/South/Southeast Asia) had the highest death counts of ICH due to PM2.5. APMP dominated in High SDI regions (e.g., Western Europe, North America, and Australasia), whereas HAP remained prevalent in low-SDI settings (e.g., Sub-Saharan Africa). Mortality disparities extended to demographics, with males experiencing 1.8 times higher ASMR than females, and the peak of fatalities shifting to older age groups (from 65–69 to 70–74 years). A strong inverse correlation emerged between SDI and the burden (ASMR-SDI: r = −0.76, p < 0.001).ConclusionAnalysis of GBD 2021 data reveals PM2.5-attributable ICH mortality in Low SDI regions is 24.7 times higher than High SDI areas, driven by HAP vs. APMP. Despite declining age-standardized rates globally (1990–2021), absolute DALYs and YLDs rose. Projections indicate burden resurgence by 2050. Considering population aging, gender and regional disparities (Asia and Sub-Saharan Africa bears highest burden), it is urgent to develop targeted strategies for APMP and HAP.